Evaluation of the First Contact Physiotherapy (FCP) model of primary care: a qualitative insight. (December 2021) - Goodwin, R.; Moffatt, F.; Hendrick, P.; Stynes, S.; Bishop, A.; Logan, P.
Abstract: Objective: First Contact Physiotherapy (FCP) is a primary care model where expert musculoskeletal (MSK) physiotherapists undertake the first patient consultation, to enhance MSK-patient care and free-up GP capacity. The authors report the qualitative findings from the FCP National Evaluation (Phase 3) which evaluated the FCP model against pre-agreed success criteria. Design and setting: A mixed-methods 24-month service evaluation involving FCP sites across England. Methods: Data were collected at 2 time points, year 1 and year 2. Data were collected using individual interviews and focus groups, transcribed verbatim and analysed using a hybrid inductive and deductive thematic analysis. Participants were recruited from all stakeholder groups; patients, physiotherapists, general practitioners and administration staff. Results: A total of 6 sites were recruited over both rounds of data collection demonstrating a wide range of service models. Thirty-nine participants were recruited including fourteen patients. All six qualitative success criteria were met. GPs' discourse reflected confidence in the FCP service and competence of the FCPs. Patient discourse reflected self-efficacy and confidence in self-management techniques and reported FCP as a positive experience. FCPs saw providing advice about work related issues as integral to their role and patient discourse reflected perceived benefit from the advice offered. Staff discourse reflected a positive experience of working with, and in, the FCP services. Conclusion: Ahead of the planned scale-up of the FCP primary care model across the UK, this evaluation provides useful insights and recommendations to facilitate successful FCP implementation in terms of patient outcome and experience, and staff experience.